Manipulative Therapy Following Standard Therapy Improves Shoulder Joint Function in Patients with Frozen Shoulder - Aditya Johan R; Heru Purbo Kuntono; Heppy Ade Kristyono (Jurnal Keterapian Fisik, 2023)
Background: Frozen shoulder is a common disorder encountered by physiotherapists, causing limited movement and pain in the shoulder joint. Many complaints experienced by patients require effective therapeutic modalities to improve joint functional ability. This study aimed to determine the effect of manipulation therapy after standard therapy on improving shoulder joint functional ability in frozen shoulder patients at Telogorejo Hospital, Semarang. Methods: This study used an experimental design with a one-group pre-test and post-test design with control, involving two groups of frozen shoulder patients. Sampling was conducted randomly with a total of 30 patients. Both groups received standard therapy in the form of TENS and ultrasound, while the treatment group received additional manipulation therapy. The measurement instrument used was the Shoulder Pain and Disability Index (SPADI) to assess pain and functional ability, which was analyzed using the Wilcoxon test. Results: The analysis showed a significant decrease in SPADI scores in the treatment group (pre-test value 62.6±6.17 decreased to post-test 44.07±5.8, p<0.05) compared to the control group (pre-test 64.4±7.58 to post-test 53.5±6.3, p<0.05). This indicates a greater improvement in functional ability and pain reduction in the treatment group. Conclusion: Manipulative therapy after standard therapy effectively improves function and reduces pain in patients with frozen shoulder. It is recommended that manipulative therapy be included in the rehabilitation protocol for frozen shoulder patients to achieve optimal therapeutic results.